Gastrostomy Tubes: Care and Feeding. Issue 12 (December 2017) - Fuchs, Susan
Abstract : Abstract: Parents often bring their children to the emergency department for adverse events with their child's gastrostomy tube or button. This review will discuss the possible complications and the methods to handle them.